Communal Education vs. The True Self Among Graduates of the Kibbutz Educational System - Keini, Noga; Helper, Amit (Advances in Social Sciences Research Journal, 2022)
This article examines the dialectic between the principles and application of communal education of the kibbutz movement and that of Winnicott’s insights of the true self. The true self is characterized by its attention towards inner mental life and its demands to fulfill its needs. The communal kibbutz education prioritized the collective needs as supreme. Many communal values were pursued in the approach and education of young members of the kibbutz in order that they prioritize the needs of the group over that of the individual. This educational approach taught young members, to attend much less to their inner emotional needs and adapt them to the needs of the community. In this article, we attempt to address, elaborate on, understand these issues and their underlying motivations needs.